Presence and quantification of the microplastics and bisphenol-A in sediments along the Guanabara Bay, Brazil - Oliveira Santos, Ana Dalva de; Lima do Nascimento, Marilia Teresa; Gomes de Carvalho, Diego; da Silva de Freitas, Alex; Hauser-Davis, Rachel Ann; Lima da Cunha, Danieli; Monteiro da Fonseca, Estefan Monteiro da Fonseca; Maia Bila, Daniele; Baptista Neto, José Antonio (Geochimica Brasiliensis, 2023)
Microplastics (MP) and endocrine disruptors, such as bisphenol-A (BPA) have both become significant environmental concerns worldwide, although assessments in estuarine environments are still scarce. In this regard, Guanabara Bay is one of the most important Brazilian estuarine systems, displaying significant economic and environmental relevance, although it has suffered increasing anthropogenic effects for decades. Thus, this study aimed to assess the occurrence of both MP and BPA in the sediments of this estuarine system though stereomicroscope identification and high-performance liquid chromatography. Both pollutants were detected in all sediment samples. A total of 3 to 11 MP particles (<5 mm) per 50 cm2 were detected, higher than in other studies worldwide. MPs were categorized as fibers and fragments, mostly green, possibly from fisher rope and net degradation. BPA ranged from 0.36 to 19.75 ng g-1, higher near Governador Island and the Rio de Janeiro harbor. Potential correlations between MPs and BPA, however, could not be determined. Both MP and BPA represent significant environmental concerns in the already highly impacted Guanabara Bay estuarine system, and further assessments are paramount to understand potential ecotoxicological hazards associated to these pollutants.